Poldip2 mediates blood‐brain barrier disruption and cerebral edema by inducing AQP4 polarity loss in mouse bacterial meningitis model. (12th August 2020) - Gao, Meng; Lu, Weitian; Shu, Yue; Yang, Zhengyu; Sun, Shanquan; Xu, Jin; Gan, Shengwei; Zhu, Shujuan; Qiu, Guoping; Zhuo, Fei; Xu, Shiye; Wang, Yiying; et al.
Abstract: Background: Specific highly polarized aquaporin‐4 (AQP4) expression is reported to play a crucial role in blood‐brain barrier (BBB) integrity and brain water transport balance. The upregulation of polymerase δ‐interacting protein 2 (Poldip2) was involved in aggravating BBB disruption following ischemic stroke. This study aimed to investigate whether Poldip2‐mediated BBB disruption and cerebral edema formation in mouse bacterial meningitis (BM) model occur via induction of AQP4 polarity loss. Methods and Results: Mouse BM model was induced by injecting mice with group B hemolytic streptococci via posterior cistern. Recombinant human Poldip2 (rh‐Poldip2) was administered intranasally at 1 hour after BM induction. Small interfering ribonucleic acid (siRNA) targeting Poldip2 was administered by intracerebroventricular (i.c.v) injection at 48 hours before BM induction. A specific inhibitor of matrix metalloproteinases (MMPs), UK383367, was administered intravenously at 0.5 hour before BM induction. Western blotting, immunofluorescence staining, quantitative real‐time PCR, neurobehavioral test, brain water content test, Evans blue (EB) permeability assay, transmission electron microscopy (TEM), and gelatin zymography were carried out. The results showed that Poldip2 was upregulated and AQP4 polarity was lost in mouse BM model. Both Poldip2 siRNA and UK383367 improved neurobehavioral outcomes, alleviated brain edema, preserved the integrity of BBB, and relieved the loss of AQP4 polarity in BM model. Rh‐Poldip2 upregulated the expression of MMPs and glial fibrillary acidic protein (GFAP) and downregulated the expression of β‐dystroglycan (β‐DG), zonula occludens‐1 (ZO‐1), occludin, and claudin‐5; whereas Poldip2 siRNA downregulated the expression of MMPs and GFAP, and upregulated β‐DG, ZO‐1, occludin, and claudin‐5. Similarly, UK383367 downregulated the expression of GFAP and upregulated the expression of β‐DG, ZO‐1, occludin, and claudin‐5. Conclusion: Poldip2 inhibition alleviated brain edema and preserved the integrity of BBB partially by relieving the loss of AQP4 polarity via MMPs/β‐DG pathway. Abstract : Schematic illustration of AQP4 polarity loss being induced by Poldip2 in mouse bacterial meningitis model. Poldip2 induced the upregulation and activation of MMPs, which mediates the cleavage of β‐DG. Due to β‐DG being responsible for AQP4 anchoring to astrocytic endfeet, the degradation of β‐DG results in AQP4 polarity loss. In the present mechanism study, Poldip2 siRNA and the UK383367 were used to inhibit Poldip2 expression and MMP activity, respectively.